Pengaruh gaya belajar terhadap hasil belajar mahasiswa PBA International Class Program angkatan 2023 dalam mata kuliah Maharah Kalam - Amin, Azkiya Rafida (Maliki Interdisciplinary Journal, 2024)
The appropriate learning style will allow individuals to easily absord information in the learning procces so that it can have a significant influence on learning outcomes. Especially in the process of learning a foreign language such as Arabic in the Maharah Kalam course. This study describes the learning styles applied by international class students and their influence on learning outcomes. The research method uses a qualitative descriptive design. Data collection techniques used observation of teaching and learning outcomes and student performance, interview wuth students, and documentation. The subjects of this research were students of the International Class Program with a total of 25 students in 2023/ data analysis uses the Miles & Huberman model, namely: data reduction, presentation and conclusion drawing/verification. The results showed that the majority of ICP class 2023 students in the Maharah Kalam course used a visual learning style. The performance of students in learning Maharah Kalam with a visual learning style in the kalam process tends to be more active but in the free storytelling process they still stammer and still use Indonesian in some words that they do not know the meaning in Arabic. While in other assigments such as describing an image using Arabic they tend to be more masterful because it is in accordance with the characteristics of the student.